IMPROVING THE SYSTEM FOR ASSESSING THE EFFECTIVENESS OF THE FINANCIAL MANAGEMENT OF AGRICULTURAL ORGANIZATIONS - Olga TAGIROVA; Alexey NOSOV; Marina FEDOTOVA; Denis MURZIN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article discusses cost models for assessing the effectiveness of financial management based on the MVA method of market value added, the EVA method, the SVA method of equity value added. The authors assessed the elements of the financial management of an agricultural organization for 2015-2019, including an evaluation of the state of fixed assets, inventories, accounts receivable, analysis of cash flows, sources of financing assets, liquidity of the balance sheet, financial stability, business profitability and business indicators of activity. For a comprehensive assessment of the effectiveness of the financial management of an agricultural organization, it was used a methodology based on the relationship of indicators, in which the indicator of economic value added acts as a criterion for the level of efficiency of financial management. A scale for quantitative and qualitative assessment of the level of financial management efficiency has been developed.